Acompanhamento farmacoterapêutico de pacientes com depressão e/ou transtornos de ansiedade em Centro de Atenção Psicossocial: do ensaio clínico à implantação do serviço - Fernandes, Sheilla Alessandra Ferreira (2020)
The pharmacist has important functions in the area of mental health, however his actions are unknown. After the Brazilian Psychiatric Reform, the priority was the implementation of substitute services and community-based mental health actions, such as psychosocial care centers (CAPS). CAPS are unique strategic units for the treatment of patients with severe mental disorders at the local level, in a multidisciplinary context. These teams include doctors, nurses, psychologists, social workers, occupational therapists, and sometimes other professionals, such as pharmacists. However, the number of pharmacists in the CAPS is insufficient for the provision of services, which are commonly linked to actions related to the technical-logistical aspects of the profession, with the technical-assistance aspect being totally neglected. Thus, the objective of this study was to implement a pharmaceutical care service, based on the Pharmacotherapeutic Monitoring (AFT) provided to patients with depression and / or anxiety disorders in a Psychosocial Care Center (CAPS). Randomized controlled clinical trial with 70 adults was developed in CAPS II of Mossoró-RN. The patients in the intervention group (IG) received the AFT service for 4 months, in parallel to the control group (CG). After the 4-month period, some patients in the CG were invited to participate for another four months receiving AFT (post-control intervention group; GIPC). Primary outcomes (treatment adherence, anxiety and depression rates, quality of life) and their variations between groups were compared. Qualitative content analysis (Bardin) applied to the interviews of patients and the CAPS health team in relation to their perceptions about the role of the pharmacist in mental health and the provision of AFT was used. The results showed that, regarding adherence to pharmacotherapy, there was a statistically significant difference in the IG, however the clinical parameters (depression and anxiety) and humanistic parameters (quality of life), did not change. For patients in the GIPC (consultations 1 to 4), when compared to moment 4 in the CG, the levels of depression decreased. According to the participants, the AFT was essential and important, as it allowed the pharmacist to be recognized, in addition to identifying the duties and work process of this professional at CAPS. There was a dual role of the pharmacist between the logistical and clinical attributes in the area of mental health. Thus, for the first time, this study showed the perceptions of patients and a health team about the role of the pharmacist and the availability of AFT in CAPS, helping to clarify the role of the pharmacist in mental health, in addition to structuring a work process clinical pharmacist to CAPS patients. In addition, this study pointed out that patients with depression and / or anxiety disorders at the CAPS should have a longer AFT in order to improve clinical and humanistic results. Finally, there is a visible need for standardized documentation and records for this pharmaceutical service for the group of patients with depression and / or anxiety disorders.